Coupling the U.K. Earth System Model to Dynamic Models of the Greenland and Antarctic Ice Sheets. (19th October 2021) - Smith, Robin S.; Mathiot, Pierre; Siahaan, Antony; Lee, Victoria; Cornford, Stephen L.; Gregory, Jonathan M.; Payne, Antony J.; Jenkins, Adrian; Holland, Paul R.; Ridley, Jeff K.; Jones, Colin G.
Abstract: The physical interactions between ice sheets and the atmosphere and ocean around them are major factors in determining the state of the climate system, yet many current Earth System models omit them entirely or treat them very simply. In this work we describe how models of the Greenland and Antarctic ice sheets have been incorporated into the global U.K. Earth System model (UKESM1) via substantial technical developments with a two‐way coupling that passes fluxes of energy and water, and the topography of the ice sheet surface and ice shelf base, between the component models. File‐based coupling outside the running model executables is used throughout to pass information between the components, which we show is both physically appropriate and convenient within the UKESM1 structure. Ice sheet surface mass balance is computed in the land surface model using multi‐layer snowpacks in subgrid‐scale elevation ranges and compares well to the results of regional climate models. Ice shelf front discharge forms icebergs, which drift and melt in the ocean. Ice shelf basal mass balance is simulated using the full three‐dimensional ocean model representation of the circulation in ice‐shelf cavities. We show a range of example results, including from simulations with changes in ice sheet height and thickness of hundreds of meters, and changes in ice sheet grounding line and land‐terminating margin of many tens of kilometres, demonstrating that the coupled model is computationally stable when subject to significant changes in ice sheet geometry. Plain Language Summary: Loss of mass from the ice sheets on Greenland and Antarctica makes an important contribution to global mean sea level (GMSL) rise, and one that will increase significantly in the coming decades and centuries. Our limited ability to predict exactly how the Earth's ice sheets will interact with the changing climate is the main reason we cannot say with confidence whether GMSL will rise by tens of centimeters or a meter or more in this century alone. One way to develop our understanding is to build tools capable of modeling the co‐evolution of ice sheets and climate, a difficult task made yet more challenging by the wide range of spatial‐ and time‐scales that need to be considered to model these systems simultaneously. UKESM1 is a state‐of‐the‐art Earth System model used to predict future climate change. Our work allows UKESM1 to be run with interactive models of the Greenland and Antarctic ice sheets. This is a new and complex model, and there are still problems to solve before such tools can be used to produce complete projections of GMSL rise. Our work nevertheless allows us to investigate new areas of climate physics in ways that have not been possible before. Key Points: A CMIP6 Earth System Model has been coupled to interactive models of both the Greenland and Antarctic ice sheets for the first time Substantial technical challenges have been overcome, our solutions and their limitations are described Our system simulates climate and ice sheet physics reasonably well, and is computationally stable when subject to extreme ice sheet retreat